Study on stress-strain relation of concrete confined by CFRP under preload. (15th July 2017) - Pan, Yi; Rui, Guo; Li, Hongyi; Tang, Hongyuan; Xu, Long
Highlights: We presents the results of 32 circular and 16 square section concrete columns confined by CFRP sheets. We analyzed the failure modes, mechanical behaviors, and some important phenomenon in columns. We got formulas of the second stiffness, lateral expansion coefficient, peak stress and strain. We report a design-oriented stress-strain model for concrete column confined by CFRP with preload. Abstract: This paper presents the experimental and analytical results of 32 circular-section and 16 square-section concrete columns confined by CFRP sheets under axial compression. The main parameters were: the preload ratio, the concrete strength and the number of CFRP piles. The failure modes, mechanical behaviors, and reasons of the descending of the peak stress and strain of the confined concrete in columns were analyzed. The experiment results indicated that the effectiveness of CFRP confinements were influenced by the preload ratio observably. Both the ultimate stress and strain decreased with the increasing of the preload ratio, and the increasing of CFRP piles will magnify the negative effect. Combined with the previous literatures, this paper concluded formulas about the second stiffness, lateral expansion coefficient, peak stress and strain of the concrete columns confined by CFRP under a certain preload ratio. Furthermore, based on these concluded formulas, a new design-oriented stress-strain model for the circular and square concrete column confined by CFRP sheets under preload was purposed respectively.